The Effects of Centella asiatica Extract (CAE) on Methamphetamine-Induced Neurotoxicity via Human Neuroblastoma Cell Line - Mazatulikhma Mat Zain Mat Zain; Nursyamila Shamsuddin; Mohd Shihabuddin Ahmad Noorden (ASM Science Journal, 2021)
Methamphetamine (METH) was reported to caused neurotoxicity and cell death, in vitro. Centella asiatica or ‘pegaga’ is a native tropical herb with antioxidant and neuroprotective activities. Although the effects of Centella asiatica against oxidative stress and neuronal cell death have been reported in previous studies, however, the potential effects of Centella asiatica against psychostimulant methamphetamine (METH) are limited. Therefore, this study was aimed to evaluate the effects of Centella asiatica extract (CAE) against METH on all-trans retinoic acid, RA-differentiated human neuroblastoma, SH-SY5Y cells. The RA-differentiated SH-SY5Y cells were used to resemble dopaminergic neuronal-like cells. Cell viability was quantitatively assessed by 3-(4,5-dimethylthiazol-2-yl)-2 tetrazolium bromide, MTS assay.  CAE at varying concentrations from 1pg/mL to 1mg/mL significantly decreased the viability of the undifferentiated SH-SY5Y cells in a concentration-dependent manner. At 1mg/mL of CAE, significantly increased the viability of differentiated SH-SY5Y cells. Meanwhile, CAE at 100µg/mL and 1mg/mL significantly reversed the METH-induced neuronal cell death. The results revealed that promising treatment of CAE on METH-induced neurotoxicity is mediated by its high content of asiaticoside, asiatic acid, madecassoside and madecassic acid. Taken together, this study may suggest CAE as a potential therapeutic treatment for METH-induced neurotoxicity, in vitro.